Internalization of Ki Suryomentaramâ€™s â€œIntrospectionâ€ in Person-Centered Counseling to Build Happiness - Rahmawati, Rizki; Utami, Ferisa Prasetyaning (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
It can be seen that individuals in Indonesia are not too happy either in young children, adults, or elderly. Troubel always come to each individual. According to Ki Suryomentaran, life is the place where we will feel sad and happy. Without any waves of problems in an individualsâ€™ life then they will not be capable of achieving welfare. Every individual is expected to have a good life by applying Carl Rodgersâ€™ Theory about perseon-centered counseling in which the counselor can help the clients understand their ability and capability in actualizing themselves and lead them to achieve happiness in their life. A Counselor can also help clients who were born with weak mentality to face the problems in their life so that they do not suffer from depression and inability to cope with those problems. Therefore, it is important to equalize individuals in achieving their present and future lives. Keywords: happiness, person-centered counseling, self awareness